2015
DOI: 10.1371/journal.pone.0128575
|View full text |Cite
|
Sign up to set email alerts
|

Haematuria Increases Progression of Advanced Proteinuric Kidney Disease

Abstract: BackgroundHaematuria has been traditionally considered as a benign hallmark of some glomerular diseases; however new studies show that haematuria may decrease renal function.ObjectiveTo determine the influence of haematuria on the rate of chronic kidney disease (CKD) progression in 71 proteinuric patients with advanced CKD (baseline eGFR <30 mL/min) during 12 months of follow-up.ResultsThe mean rate of decline in eGFR was higher in patients with both haematuria and proteinuria (haemoproteinuria, HP, n=31) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…In addition to being cytotoxic, heme can promote renal damage by inducing inflammation and fibrosis . Multiple episodes of macroscopic hematuria are associated with a decline in renal function and progression of chronic renal disease . Reducing macroscopic hematuria may thus improve renal function and limit future renal damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being cytotoxic, heme can promote renal damage by inducing inflammation and fibrosis . Multiple episodes of macroscopic hematuria are associated with a decline in renal function and progression of chronic renal disease . Reducing macroscopic hematuria may thus improve renal function and limit future renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Multiple episodes of macroscopic hematuria are associated with a decline in renal function and progression of chronic renal disease. [27][28][29] Reducing macroscopic hematuria may thus improve renal function and limit future renal damage. Although management of macroscopic hematuria depends on etiology, the recommended initial treatment is increased fluid intake, either orally or by intravenous hydration.…”
Section: Discussionmentioning
confidence: 99%
“…Capillary wall injury in few glomeruli can produce hematuria. 56,57 It remains uncertain if persistent hematuria always originates from vascular lesions of the same glomeruli that do not heal or whether clots stop bleeding in some glomeruli, whereas others start to bleed with persistent hematuria as a net effect. IgA nephropathy as well as other renal disorders present with episodes of intermittent macrohematuria that can last several days, suggesting insufficient clotting.…”
Section: Insufficient Clotting In Kidney Diseasementioning
confidence: 99%
“…The damage induced by hematuria does not appear to be unique to IgAN, as recently reported by the same investigators who found hematuria to be closely associated with more rapid decline in eGFR in a variety of proteinuria disorders other than IgAN, especially in younger patients. 21 Although persistent proteinuria can reflect active capillary and podocyte lesions, it can also be due to hyperfiltration in chronic, irreversible cases. In IgAN, proteinuria by itself cannot discriminate between active inflammation versus chronic damage.…”
mentioning
confidence: 99%